A NiCo2O4@Ni–Co–Ci core–shell nanowire array as an efficient electrocatalyst for water oxidation at near-neutral pH. Issue 55 (27th June 2017) - Ge, Ruixiang; Ma, Min; Ren, Xiang; Qu, Fengli; Liu, Zhiang; Du, Gu; Asiri, Abdullah M.; Chen, Liang; Zheng, Baozhan; Sun, Xuping
Abstract : Core–shell structured NiCo2 O4 @Ni–Co–Ci/CC drives 10 mA cm −2 at 309 mV overpotential for water oxidation in 1.0 M K–Ci. Abstract : It is attractive but still remains challenging to develop efficient water oxidation electrocatalysts working in a carbonate (Ci) electrolyte. In this communication, we report that a Ni–Co–Ci layer can be developed on a NiCo2 O4 nanowire array supported on carbon cloth (NiCo2 O4 /CC) via electrochemical surface derivation of NiCo2 O4 . The resulting NiCo2 O4 @Ni–Co–Ci core–shell nanowire array on carbon cloth (NiCo2 O4 @Ni–Co–Ci/CC) exhibits high activity toward water oxidation in 1.0 M KHCO3 (K–Ci, pH = 8.3) with the overpotential requirement of 309 mV to drive 10 mA cm −2 . NiCo2 O4 @Ni–Co–Ci/CC also shows long-term electrochemical stability for 20 h and a high turnover frequency of 0.464 mol O2 s −1 at an overpotential of 600 mV.